SiO2 particles effect on the mechanical properties of the starch/PVA blends - Nahida J. H. (Iraqi Journal of Physics, 2018)
The present work studies the mechanical properties of SiO2 μPs, and NPs in St/PVA blends. The samples were prepared by casting method as PVA, St/PVA blends at different concentrations (30, 40, 50, and 60 %). DSC and TGA tests were carried out to the samples evolved. The result showed a single glass transition temperature (Tg) for all St /PVA blends that was attributed to the good miscibility of the blends involved. It was found that (Tg) decrease with starch ratio increase. It was seen that (PVA) of (Tg=105 oC); The glass transition temperature which was decrease with starch ratio that was attributed to glass transition relaxation process due to micro-Brownian motion of the main chain back bond. The endothermic peak at 200 oC was attributed to melting point of (PVA). Thermal properties of PVA; and St /PVA blends at different concentration (30, 40, 50, and 60 %) were evaluated by thermo gravimetric analysis (TGA). The analyses were carried out from 20 to 600 oC at 10 oC)/min heating rate in air oxygen atmosphere. The weight loss stages depended on polymer system. The starch addition causing shifting in the second degradation temperature to the higher temperature; which result in overlapping between the two main degradation steps, these result was attributed to the St/ PVA blend compatibility. The mechanical properties results showed a decrease in ultimate strength with starch ratio increase. The ultimate strength of (PVA) was (47 MPa), whereas the ultimate strength of 60 %St/PVA was (11 MPa) and for 30 %St/PVA was the highest ultimate strength of blends involved (26 MPa). SiO2μPs (753.7 nm), and NPs (263.1 nm) were added at different concentrations (1.5, 2, and 2.5 %). 1.5% SiO2μPs, and NPs of the best ultimate strength (69 MPa), (86 MPa) respectively then it was decreased by SiO2μPs, and NPs increase. Optical microscope of the samples involved was investigated. It was concluded the prepared samples were suggested to be used as packaging materials for agriculture application and its ultimate strength could be controlled by SiO2μPs, and NPs addition.